2021
DOI: 10.1016/j.jaad.2020.04.171
|View full text |Cite
|
Sign up to set email alerts
|

Use of teledermatology by dermatology hospitalists is effective in the diagnosis and management of inpatient disease

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…A prospective study on teledermatology found that the primary diagnosis given by a virtual consult was concordant with that of an in-person consult in 67% of cases. 3 Although the methodologies of our study and the study by Gabel et al 3 are too disparate to directly compare results, our experience indicates that further research on inpatient teledermatology and the criteria for which it might be safely and effectively used is warranted.…”
mentioning
confidence: 68%
“…A prospective study on teledermatology found that the primary diagnosis given by a virtual consult was concordant with that of an in-person consult in 67% of cases. 3 Although the methodologies of our study and the study by Gabel et al 3 are too disparate to directly compare results, our experience indicates that further research on inpatient teledermatology and the criteria for which it might be safely and effectively used is warranted.…”
mentioning
confidence: 68%
“…Our findings are consistent with the current literature, which has validated store-and-forward teledermatology as an effective care delivery model for inpatient dermatology. 5 The limitations of this study need to be acknowledged. Our study population was restricted to acute respiratory illness/suspected COVID-19 cases.…”
Section: Early Experience Of Inpatient Teledermatology In Singapore During Covid-19mentioning
confidence: 95%
“…2,4 Nonetheless, a small prospective study proposed by Gabel et al showed that teledermatology in the inpatient setting might be an acceptable option for diagnosis, evaluation and management. 5 Singapore was one of the first countries to report imported COVID-19 cases in early 2020, with subsequent government public health measures to contain the spread. 6 Many restructured hospitals reorganised inpatient care, segregated resources, including reserving negative pressure rooms for suspected COVID-19 patients.…”
Section: Early Experience Of Inpatient Teledermatology In Singapore During Covid-19mentioning
confidence: 99%
“…However, recent studies are demonstrating its effectiveness for inpatient dermatology as well [4]. Because inpatient access to dermatologists is typically limited, teledermatology represents a novel solution to this long-standing accessibility problem [8]. When dermatologists perform inpatient consults, the patient outcomes are largely improved; similarly, inpatient teledermatology functions to reduce the wait time for a patient to receive such care [8] (14).…”
Section: Teledermatology In Inpatient Servicesmentioning
confidence: 99%